Comparison of manual data coding errors in two hospitals. Issue 6 (June 1986) - Hall, P A; Lemoine, N R
Abstract : The routine manual encoding of pathological data, using the SNOP and SNOMED systems at two London teaching hospitals, was reviewed. The error rates in the two departments were compared and the causes analysed. The relative merits of SNOP and SNOMED were considered. Methods to optimise the efficiency of manual encoding are suggested and the importance of accuracy in coding is emphasised.